Sociedade civil e os programas de reabilitação do patrimônio: o caso dos programas Monumenta e PAC Cidades Históricas em Ouro Preto - Carla Neves Almeida Gomes (2016)
This research aims to evaluate the civil societys participation in policies related to the heritage management. For research, we chose a case study that addresses Programa Monumenta and Programa de Aceleração do Crescimento das Cidades Históricas, in Ouro Preto, as they aim the increase of knowledge about the heritage and the participation of people in different stages of its management, respectively. In order to identify some previous social participation in the context of policies related to heritage in the city, a documental analysis was performed, as well as interviews with the competent bodies. The population also responded to forms, in this case we chose a geographic limit, which included the residents of Pilar and Antonio Dias neighborhoods, for being inserted in the urban perimeter recognized as a national and World Cultural Heritage and also for the relevance of them in the historical context of the city. A literature review on the importance of social participation and the way it happens allowed the final reflection of this work that questions if the representativeness of civil society in discussions related to the heritage management is effective and the role of municipal government as the responsible for the promotion of discussion with this population.